Melodia: A Python Library for Protein Structure Analysis. - Montalvão, Rinaldo W; Pitt, William R; Pinheiro, Vitor B; Blundell, Tom L (Oxford University Press (OUP), 2024)
SUMMARY: Analysing protein structure similarities is an important step in protein engineering and drug discovery. Methodologies that are more advanced than simple RMSD are available but often require extensive mathematical or computational knowledge for implementation. Grouping and optimising such tools in an efficient open-source library increases accessibility and encourages the adoption of more advanced metrics. Melodia is a Python library with a complete set of components devised for describing, comparing and analysing the shape of protein structures using differential geometry of three-dimensional curves and knot theory. It can generate robust geometric descriptors for thousands of shapes in just a few minutes. Those descriptors are more sensitive to structural feature variation than RMSD deviation. Melodia also incorporates sequence structural annotation and three-dimensional visualisations. AVAILABILITY AND IMPLEMENTATION: Melodia is an open-source Python library freely available on https://github.com/rwmontalvao/Melodia_py, along with interactive Jupyter Notebook tutorials. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Acknowledgements: R.W.M. would like to thank Antonio Marinho da Silva Neto and Samuel Reghim Silva for their helpful suggestions when preparing this library.
Keywords: artificial intelligence; differential geometry; knot theory; proteins; structure analysis